Long-term assessment of risk factors for canine tumors registered in Xi'an, China - Wei Wang; Weihui Li; Dianfeng Chu; Jinlian Hua; Xinke Zhang; Dezhang Lu; Yan Wang; Shiqiang Zhang (BMC, 2021)
Abstract Tumors are one of the leading causes to death in pet dogs among diseases. The tumor incidence of pet dogs has been increasing, raising widespread concern.The tumor incidence of pet dogs has been increasing, raising widespread concern. In this study, retrospective analysis was performed with 246 tumor cases registered in Xi'an Animal Hospital, Northwest A&F University from 2009 to 2018. Correlations of sex, age and breed with tumor incidences were evaluated. The results showed that reproductive system tumors occupied the highest proportion (39.84%), followed by cutaneous tumors (28.05%), digestive tumors (18.70%) and ocular tumor (4.47%). Among the reproductive system tumors, breast tumors are the most common tumor in female pet dogs, especially for Pekingese (11.43%). Female dogs with high susceptibility to breast tumors were at the ages of 6-18 years old. As far as cutaneous tumors were concerned, the male pet dogs at all ages, particularly Golden Retrievers (17.39%), showed a high incidence. By contrast, male Samoyed aged from 4 to 13 years had the highest incidence (15.22%) of digestive tumors. In addition, pet dogs with ocular tumors mainly happened at the ages of 0-1 years and 6-13 years. Collectively, our findings are significant to develop effective measures of medical surveillance for pet dogs' health and will provide insights for comparative oncology.